Mafhūmu Fiqhi al-Marātib wa Fiqhi al-Awlawiyyāt fī Maqāṣidi al-Qurʾān: Dirāsah Taṭbīqiyyah fī Malaysia - Ahmad, Siddig; Ahmad Sunawari Long; Zaizul Ab. Rahman; Muhammad Taufiq; Hüseyin Elmhemit (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2024)
The debate on the concept of maqāṣid continues to develop dynamically as its relevance to various situations and times. However, misunderstanding the basic principles of maqāṣid which are fixed (al-thawābit) and flexible (al-mutaghayyirāt) causes neglect of one aspect of the basic principles of maqāṣid, and unconsciously leading into dichotomy between the two. Ironically, religious understanding derived from it loses its spirit while maqāṣid is only for the sake of worldly interests while ignoring afterlife mission. This study aims to explain the universal (kullī) and particular (juz’ī) principles of maqāṣid and identify the right approach to implement both principles at the International Islamic University Malaysia. This research used a qualitative approach whose data is obtained through various sources such as observation at the locus, books, journals, conference papers, and relevant websites. The data obtained were analyzed descriptively. This study found that the debate on maqāṣid must be contextualized by understanding the purposes of the Qur'an (maqāṣid al-Qur'ān) which includes the debate on the two principles of maqāṣid. In the discourse of maqāṣid al-Qur'ān, the discussion of maqāṣid al-Sharīʿah is a part that is particular and flexible (al-mutaghayyirāt). This research also found that the right approach to implement maqāṣid al-Qur'ān is with the fiqh of command (fiqh al-marātib). Conversely, the right approach to implementing maqāṣid al-Sharīʿah is with priority fiqh (fiqh Al-Awlawiyyāt). The integration of the two is practiced and implemented in the International Institute of Islamic Thought and Civilization, International Islamic University Malaysia with a context that is very relevant to the context of fiqh that develops in Malaysia.